Super-exponential methods for blind detection of asynchronous CDMA signals over multipath channels. - Tongtong Li (IEEE Transactions on wireless communications)
In this letter, code-constrained super-exponential algorithms (CSEA) are presented for blind detection of asynchronous short-code direct-sequence code-division multiple-access signals over multipath channels. Constrained SEA leads to the extraction of the desired user whereas unconstrained SEA leads to the extraction of any one of the actives users. The results are further improved by following the constrained SEA by unconstrained SEA. Convergence of the constrained SEA is proved and simulation examples are provided to illustrate the proposed approaches.